IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 8 TAHUN 2011 TENTANG PAJAK AIR TANAH (TELAAH PASAL 5 AYAT 5) - Desy Veronica Girsang; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Tax policy implementation of the groundwater in the city of Semarang is fully set forth in the applicable local number 8 Year 2011 Tax On groundwater. The authorized agency in terms of management of this groundwater is tax Agency income area of Semarang (Bapenda). The inception of local regulations that govern the tax on groundwater is one of the efforts to maintain the sustainability and curbing the use of groundwater, in order to be used on an ongoing basis and perform tax as a source of income the State useful for development. This research aims to describe how the implementation of the regional city of Semarang number 8 Year 2011 Tax of Groundwater in particular of article 5 paragraph 5 as well as know the factor endowments and the regulatory barrier to the area. Type of this research is descriptive research with qualitative approach method. The results showed in the implementation regulations of the area found that the content of the regulation area is seen from the base of the imposition and tax rates, the procedures for voting, the voting, and tax calculations, procedures, assignment of payment billing, tax, objection or appeal, as well as administrative sanctions have not been effective. In this study also found supporters and restricting factors i.e. standard regional income agency city of Semarang, resources, implementing agent character, communication between environmental organizations, and economic, social, political. Recommendations that can be given is the increased intensity of the socialization of local regulations, strengthening coordination between the implementing parties, increased human resources, cooperation with other parties to support the implementation of local regulations such.